philosophical dissertations about the origin of qualitative research (Revista Electrónica REDINE, 2018)
The following research aims to establish the inherent philosophical foundations of qualitative research, taking an argumentative and reflexive approach about the different concepts based on the scientific perspective and the emerging postulates.  So that, the type of research is documentary, through the writing of an argumentative essay, which is focused on a comprehensive review of the theories and approaches found from various literature sources. Also, the methodology to be assumed at the time of speech development based on the phenomenological model. So, three criteria are established in order to organize the discourse: dialogical scenario, true concept and language. It is important to say that the interpretation of the information obtained will allow show the importance of epistemological and ontological conception in the understanding of qualitative research and application of new knowledge to improve the research process.
Keywords: philosophical foundations; qualitative research; speech; phenomenology